A „Gondviselés fia” – Márton Áron püspökké szentelésének néhány előzménye a korabeli erdélyi sajtóban - KISS, Endre (Studia Universitatis Babes-Bolyai Theologia Reformata Transylvanica, 2024)
The “Son of Providence” – Some Background to the Episcopal Consecration of Áron Márton in the Transylvanian Press of the Time The consecration of Áron Márton as bishop was an unusual event in the life of the parish of Cluj-Napoca. His attachment to the parish and the organization of the ecclesiastical infrastructure of Cluj-Napoca led Áron Márton to be consecrated Bishop of Alba Iulia (Gyulafehérvár) on 12 February 1939 in the Church of St Michael in Cluj-Napoca. Áron Márton’s appointment as bishop was preceded by his appointment as apostolic administrator. He had to take over the governance of the Diocese of Alba Iulia under difficult circumstances, as the Dutch loan was a heavy burden on the parish of St Michael in Cluj-Napoca. The press releases preceding and accompanying the consecration of a bishop carefully cover the events leading up to, during, and following the consecration. In the first part of my short study, I will focus on some of the interesting press releases that preceded the consecration of Áron Márton as bishop, as well as on the major events of the days immediately preceding the consecration, and then briefly describe the consecration and the receptions and greetings that followed.